ISSUES OF FORMATION OF RELIGIOUS CULTURE AND SPIRITUAL AND MORAL CONSCIOUSNESS OF YOUTH (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article is devoted to the analysis of religiousness of youth in Kyrgyzstan. The reasons of the religious Renaissance in Kyrgyzstan are shown in sovereignization conditions. The relation of modern youth to religion is considered in the republic. It is characterized features of religiousness of the Kyrgyz youth in the conditions of formation of polyconfessional society. On the basis of sociological survey of students in the city of Bishkek various aspects of coverage are shown by religiousness, in particular Islam to youth in the Kyrgyz republic in guanfitative and gualitative aspect. The growing tendencies to polization and radicalization of Islam in Kyrgyzstan are revealed. Mechanisms of prevention and control of distribution of radical currents of Islam in Kyrgyzstan are specified.
Keywords: religion, religiosity of youth, Islam, orthodoxy, religious culture, moral, protestantism, religious extremism.